2012
DOI: 10.1002/jbmr.1628
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast maturation and new bone formation in response to titanium implant surface features are reduced with age

Abstract: The surface properties of materials contribute to host cellular response and play a significant role in determining the overall success or failure of an implanted biomaterial. Rough titanium (Ti) surface microtopography and high surface free energy have been shown to enhance osteoblast maturation in vitro and increase bone formation in vivo. While the surface properties of Ti are known to affect osteoblast response, host bone quality also plays a significant role in determining successful osseointegration. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 35 publications
0
53
0
1
Order By: Relevance
“…We have employed the hEB model for hESC differentiation to obtain hMSC population. Several different techniques have been reported that induce differentiation of hESC toward osteogenic lineages including EB formation [27][28][29], monolayer differentiation [30][31][32][33], through coculture with OP9 cells [3,6,31,32,34] or fibroblasts [35]. Although monolayer and coculture methods may increase homogeneity of cells during differentiation, they fail to recapitulate the morphological changes occurring in a more ''natural'' context that is provided during EB differentiation [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…We have employed the hEB model for hESC differentiation to obtain hMSC population. Several different techniques have been reported that induce differentiation of hESC toward osteogenic lineages including EB formation [27][28][29], monolayer differentiation [30][31][32][33], through coculture with OP9 cells [3,6,31,32,34] or fibroblasts [35]. Although monolayer and coculture methods may increase homogeneity of cells during differentiation, they fail to recapitulate the morphological changes occurring in a more ''natural'' context that is provided during EB differentiation [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of implant surface wettability transcends its role at the protein and cellular level, and has been confirmed in vivo and in the clinic [11, 28, 42, 61, 85, 121123]. Hydrophilic surfaces of experimental, relatively smooth (R a < 0.8 μm) disk-shaped Ti implants were shown to promote early bone formation compared to hydrophobic surfaces [28].…”
Section: Impact Of Wettability: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Finally, Olivares-Navarrete et al studied if the effects of surface characteristics such as surface roughness and wettability could be affected by age in a novel murine femoral intramedullary bone formation model using machined, BAE and modBAE implants [123]. The results revealed that after 4 weeks the old mice (9-month old) developed significantly higher bone-to-implant contact on modBAE surfaces compared to machined surfaces, in contrast to younger mice (2-month old), which presented similarly high levels on all three surfaces.…”
Section: Impact Of Wettability: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…The effects of hyperlipidemia on bone health may also interfere with dental implant therapy since the host’s bone quantity, quality and healing potential play an important role in osseointegration(Fedele, Sabbah et al 2011; Gaetti-Jardim, Santiago-Junior et al 2011; Olivares-Navarrete, Raines et al 2012). Currently, the role of hyperlipidemia in implant osseointegration is unknown.…”
Section: Introductionmentioning
confidence: 99%